International Journal of Advanced Science and Technology Vol. 29, No.7, (2020), pp. 9667-9671 - Leena Pal, Dr. Harish Kumar Tyagi (International Journal of Advanced Science and Technology, 2020)
The era we are living in today is a digital era. We just cannot imagine a second moment without digital connectivity. Each one of us be it a child, an adolescent or an adult, technology has become an integral part of our day to day life. Each aspect of our life is dependent on some or the other way. School going children are also experiencing the same specially the adolescent children. Though they use it to widen their horizons in multiple aspects of life but in that due to unawareness they get trapped into the vicious circle, which is often difficult for them to break without any expert help. Cyber crime is conducted using computer and internet. It is the crime which is far dangerous than the war with weapons. Each day we hear of some new application for some aspect which sounds interesting to us and we download it without knowing the repercussions of it. In present time it is the data theft which is the cause of concern. Each one of us needs to be aware of cyber security. Since India is transforming to digitization at a faster rate, our youth is far more vulnerable to get entrapped in cyber crimes due to lack of awareness of cyber laws. Our children fall prey to cyber bullying, cyber stalking, identity theft, online abuse, online gaming threats and what not.